Ore-Forming Fluid Evolution of Shallow Polyhalite Deposits in the Kunteyi Playa in the North Qaidam Basin - Yuan, Xiaolong; Meng, Fanwei; Zhang, Xiying; Sheng, Jinchang; Galamay, A. R.; Cheng, Huaide; Li, Yongshou; Miao, Weiliang; Li, Wenxia; Tang, Qiliang; Li, Jun; Du, Yongsheng (Frontiers in Earth Science, 2021)
Polyhalite occurrence in the Kunteyi Playa in the Qaidam Basin has been known for many years. However, the genetic mechanism of this deposit remains unclear. In this study, a typical section in the playa depocenter is selected to study the polyhalite mineralogy combined with the homogenization temperature and composition of halite fluid inclusions in shallow evaporitic strata. The results show that (1) the main evaporite minerals in the strata are halite and polyhalite; no common gypsum is found; (2) analyses of homogenization temperatures of halite fluid inclusions indicate that a higher temperature is needed for polyhalite generation compared with other saline minerals, and (3) the fluid inclusion chemical analysis shows that they are sulfate-type minerals with a shortage of Ca. Thus, it can be concluded that the formation of polyhalite is not related to gypsum replacement, and deep oilfield brines may provide a Ca source and a higher temperature for polyhalite formation, where the mixing and interaction occurred between K- and Mg-enriched sulfate brines and deep Ca-enriched brines under the control of climate and tectonics in the study area. While most polyhalite was generated natively, some formed during secondary generation, which was potentially related to replacement with carnallites or sylvites.